Comunicação ao SETAC (Society of Environmental Toxicology and Chemistry) Europe 17th Annual Meeting - Ferreira, Rui Manuel Alves (2008)
Heavy metal exposition has been shown to alter in several cases cellular redox status in various cell types. Activiation or inactiviation of various antioxidants enzymes were also reported during insult as well as during oxidative stress. In yeast glutathione reductase (GR, E.C. 1.6.4.2), an important antioxidant enzyme which maintain the reduced status of the cell, reveals 49.8% aa identity when compared with Escherichia coli and human GR sequences. In a previous study we has been observed an in vivo decrease on GR activity of yeast cells grown in presence of ammonium metavanadate, ranging from 0,75-7,5 mM. Here, we examined the in vitro effects of ammonium metavanadate on the GR activity from wild wine S. chevalieri. At 37ÂºC, GR was inhibited by vanadium salt in a concentration-dependent manner, with 50% inhibition at 0,4 mM ammonium metavanadate. These results support the hypothesis that vanadium salt disturbs the function of GR by a post-translational mechanism.